Subnational Debt Management Performance Assessment Methodology - World Bank Group (World Bank, Washington, DC, 2016)
The Subnational DeMPA is a methodology for assessing subnational debt management performance at the level of local government through a comprehensive set of indicators spanning the full range of subnational debt management functions. The SN DeMPA methodology was revised and aligned to the updates of the sovereign DeMPA during 2015. The objective of the 2016 update of Subnational DeMPA methodology is to revise the evaluation criteria in line with the changing practices for subnational government debt management and requirements of the client countries, as well as to take into account revised criteria of the sovereign DeMPA methodology which took place in 2015. The revised methodology combines the original SN DeMPA Tool and Guide into one unified methodological framework. Substantial revisions and additions are made in order to address the issues that arose during the earlier assessments. A revised Subnational DeMPA tool (2016) comprises of five core areas, 13 DPIs and 31 dimensions, which are applied to evaluate the capacity of the subnational borrower to manage the debt portfolio. This methodology is applied starting September 2016. For any additional information or questions, please contact: Lilia Razlog, Senior Debt Specialist, E-mail: lrazlog@worldbank.org